Economic Evaluation of Catheter Ablation of Atrial Fibrillation in Patients with Heart Failure With Reduced Ejection Fraction. Issue 12 (December 2020) - Chew, Derek S.; Loring, Zak; Anand, Jatin; Fudim, Marat; Lowenstern, Angela; Rymer, Jennifer A.; Weimer, Kristin E.D.; Atwater, Brett D.; DeVore, Adam D.; Exner, Derek V.; Noseworthy, Peter A.; Yancy, Clyde W.; et al.
Abstract : Background: Randomized clinical trials have demonstrated that catheter ablation for atrial fibrillation in patients with heart failure with reduced ejection fraction may improve survival and other cardiovascular outcomes. Methods: We constructed a decision-analytic Markov model to estimate the costs and benefits of catheter ablation and medical management in patients with symptomatic heart failure with reduced ejection fraction (left ventricular ejection fraction ⩽35%) and atrial fibrillation over a lifetime horizon. Evidence from the published literature informed the model inputs, including clinical effectiveness data from meta-analyses. Probabilistic and deterministic sensitivity analyses were performed. A 3% discount rate was applied to both future costs and benefits. The primary outcome was the incremental cost-effectiveness ratio assessed from the US health care sector perspective. Results: Catheter ablation was associated with 6.47 (95% CI, 5.89–6.93) quality-adjusted life years (QALYs) and a total cost of $105 657 (95% CI, $55 311–$191 934; 2018 US dollars), compared with 5.30 (95% CI, 5.20–5.39) QALYs and $63 040 (95% CI, $37 624–$102 260) for medical management. The incremental cost-effectiveness ratio for catheter ablation compared with medical management was $38 496 (95% CI, $5583–$117 510) per QALY gained. Model inputs with the greatest variation on incremental cost-effectiveness ratio estimates were the cost of ablation and the effect of catheter ablation on mortality reduction. When assuming a more conservative estimate of the treatment effect of catheter ablation on mortality (hazard ratio of 0.86), the estimated incremental cost-effectiveness ratio was $74 403 per QALY gained. At a willingness-to-pay threshold of $100 000 per QALY gained, atrial fibrillation ablation was found to be economically favorable compared with medical management in 95% of simulations. Conclusions: Catheter ablation in patients with heart failure with reduced ejection fraction patients and atrial fibrillation may be considered economically attractive at current benchmarks for societal willingness-to-pay in the United States. Abstract : Supplemental Digital Content is available in the text.